2015
DOI: 10.3923/ajas.2016.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Profiling of Rumen Fermentation and Microbial Population Changes in Goats Fed with Napier Grass Supplemented with Whole Corn Plant Silage

Abstract: The effects of different inclusion level of whole corn plant silage to Napier grass were observed in determining rumen fermentation and microbial population in goats. Fifteen male Boer cross goats around six months old of approximately 18.54±1.83 kg of b.wt., were used as experimental animals. The goats were assigned into five groups with three goats per treatment group. The five treatment groups consisted of different proportions of Napier Grass (G) and whole corn plant silage (CS)-G/CS, (T1) 100/0, (T2) 75/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
8
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 47 publications
4
8
1
Order By: Relevance
“…In our research, corn silage, because of its relatively high content of easily digestible NSC, caused a higher intensity of microbial fermentation in ruminal fluid than in SS samples, which resulted in a higher VFA concentration with decreased acetic and increased propionic and butyric acid molar proportions. These effects correlate with the study by Khaing et al [35], which showed that increasing the proportion of corn silage in a goat diet resulted in increased molar proportions of propionic and butyric acids and a decreased proportion of acetic acid in the ruminal fluid.…”
Section: Discussionsupporting
confidence: 90%
“…In our research, corn silage, because of its relatively high content of easily digestible NSC, caused a higher intensity of microbial fermentation in ruminal fluid than in SS samples, which resulted in a higher VFA concentration with decreased acetic and increased propionic and butyric acid molar proportions. These effects correlate with the study by Khaing et al [35], which showed that increasing the proportion of corn silage in a goat diet resulted in increased molar proportions of propionic and butyric acids and a decreased proportion of acetic acid in the ruminal fluid.…”
Section: Discussionsupporting
confidence: 90%
“…The values obtained in the present study for pH accordance to be conducive for the rumen microbes (fauna) and also enhanced faunation in the rumen. This is in agrement with the earlier study of Khaing et. al.…”
Section: Effect Of Dietary Treatments On Feed Intake and Microbial Activities In Growing Sheep Fed Total Mixed Rationsupporting
confidence: 91%
“…The rumen cellulolytic bacteria microbes present in this present study showed greater degradation of fibre. This is in support of Khaing (2016), who reported that some various rumen cellulolytic bacteria have better capacity to degrade fibre materials. It was also recorded in the present study, that there were increase occurrences of B. succinogen, Lactobaccillus, S. pneumonia and R. flavefaciens were comparable among the dietary treatments.…”
Section: Effect Of Dietary Treatments On Feed Intake and Microbial Activities In Growing Sheep Fed Total Mixed Rationsupporting
confidence: 88%
“…The pH is an efficient marker of rumen metabolism (Khaing et al, 2016). The ruminal fluid pH is probably the most important ruminal factor affecting microbial population and their activities (Nagaraja, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…The ruminal concentration of ammonia nitrogen is an effective indicator of microbial activity in the rumen (Adeyemi et al, 2016;Khaing et al, 2016). The minimum concentration of ammonia nitrogen needed for microbial protein synthesis is 5-7 mg/dl (NRC, 1985) while the concentrations in the range of 10 -20 mg /dl is needed for optimum fibre degradation in the rumen (Leng, 1990).…”
Section: Discussionmentioning
confidence: 99%